2018
DOI: 10.1108/ci-06-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and improvement of labor productivity using hybrid system dynamics and agent-based modeling approach

Abstract: Purpose The purpose of this paper is to present a hybrid simulation approach for predicting the value of labor productivity taking account of various continuous influencing factors and the interactions between different agents involved in the project. Design/methodology/approach The various continuous factors affecting labor productivity are simulated using system dynamics (SD). The heterogeneity of different agents involved in the project and their interactions is accounted using agent-based modelling (ABM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…There was a constant flow of information between the models (Nasirzadeh et al, 2018). Khanzadi et al (2017) also used an integrated SD-ABM simulation approach to see how site congestion affects productivity.…”
Section: Hybrid Simulation Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a constant flow of information between the models (Nasirzadeh et al, 2018). Khanzadi et al (2017) also used an integrated SD-ABM simulation approach to see how site congestion affects productivity.…”
Section: Hybrid Simulation Approachesmentioning
confidence: 99%
“…Since then, several different approaches have been proposed. The existing literature on construction simulation mostly uses one of the following as case studies: earthworks -e.g., AbouRizk and Halpin (1992), Lorterapong and Moselhi (1996), and Alzraiee et al (2012); reinforced concrete works -e.g., Moradi et al (2015), Khanzadi et al (2017), and Nojedehi and Nasirzadeh (2017); or civil engineering works -e.g., AbouRizk and Sawhney (1993), Robinson Fayek and Oduba (2005), and AbouRizk (2010), which are mostly machinedriven works. However, it is arguably more important to simulate labor-driven operations because labor resources (especially skilled) tend to be scarcer and contain more risk than do equipment or materials.…”
Section: Introductionmentioning
confidence: 99%
“…Khanzadi et al [41] suggested an SD-ABM hybrid simulation approach to improve productivity. The SD component contained the influencing factors, while the ABM part had groups of workers as agents and was used to model site congestion.…”
Section: Use Of Simulation For Productivity Studiesmentioning
confidence: 99%
“…There was constant information flow between the models [34]. Khanzadi et al [6] also used an integrated SD-ABM simulation approach to see how site congestion affects productivity.…”
Section: The Possible Combinations Of the Basic Simulation Approachesmentioning
confidence: 99%
“…Most of the existing literature on construction simulation introduces earthworks (see, for example, AbouRizk and Halpin [3], Alzraiee, Zayed and Moselhi [4], Lorterapong and Moselhi [5]), reinforced concrete works (see, for example, Khanzadi et al [6], Moradi, Nasirzadeh and Golkhoo [7], Nojedehi and Nasirzadeh [8]) or civil engineering works (see, for example, AbouRizk and Sawhney [9], AbouRizk [10], Robinson Fayek and Oduba [11]) as case studies, which are mostly machine-driven works. However, it is arguably more important to simulate labour-driven works as labour resources tend to be scarcer (especially skilled) and more risks are involved with them than with equipment or materials.…”
Section: Introductionmentioning
confidence: 99%